2019
DOI: 10.1021/acsomega.9b01476
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Atmospheric Pressure Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry Adds Enhanced Functionalities to MALDI MS Profiling for Disease Diagnostics

Abstract: A liquid matrix-assisted laser desorption/ionization (liquid MALDI) method has been developed for high-throughput atmospheric pressure (AP) mass spectrometry (MS) analysis of the molecular content of crude bioliquids for disease diagnostics. The presented method is rapid and highly robust, enabling its application in environments where speed and low-cost high-throughput analyses are required. Importantly, because of the creation of multiply charged analyte ions, it provides additional functionalities that conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Therefore, a new milk preparation method was developed capable of the detection of both lipids and larger hydrophilic biomolecules such as larger peptides and proteins/proteoforms. In short, a conventional TCA precipitation preparation was applied which also retained a sufficient number of lipids 13 . Figure 2 shows two liquid AP-MALDI mass spectra that were acquired with this new milk sample preparation, displaying singly charged lipids up to m/z 900 and multiply charged peptides and proteins above m/z 800 for cow milk and goat milk, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a new milk preparation method was developed capable of the detection of both lipids and larger hydrophilic biomolecules such as larger peptides and proteins/proteoforms. In short, a conventional TCA precipitation preparation was applied which also retained a sufficient number of lipids 13 . Figure 2 shows two liquid AP-MALDI mass spectra that were acquired with this new milk sample preparation, displaying singly charged lipids up to m/z 900 and multiply charged peptides and proteins above m/z 800 for cow milk and goat milk, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Liquid MALDI samples provide robust and stable ion signal yields 12 of metabolites, lipids and multiply charged proteinaceous analytes 10 in the same analysis/spectrum. This analytical feature together with the possibility to sequence proteins of interest directly from the same MALDI sample by rapidly switching to CID (and potentially ECD/ETD) MS/MS is currently unique for MALDI MS profiling analysis 13 . The combination with a purpose-built machine learning tool based on Linear Discriminant Analysis (LDA) allows for the real-time recognition of milk from different species and the detection of 5% of cow milk in goat milk at high accuracy.…”
mentioning
confidence: 99%
“…There is a high level of similarity between the milk and the intra mammary microbiome, therefore, the milk microbiome represents a good source of information about the intra-mammary environment. Such environment is altered during mastitis events and produces major changes in the milk microbiome and in the composition/integrity of the milk proteome [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, liquid AP-MALDI MS is well suited for the detection of peptides and proteins as it produces multiply charged peptide and protein ions [21]. All this can be achieved with a simple one-pot sample preparation [29]. Using liquid MALDI with its liquid sample droplets also avoids the typical search for sample "sweet spots" to achieve optimal desorption/ionisation and provides superior ion yield stability [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be concluded that β-lactoglobulin was detected in the MS profiles of both species and can be used as a species–specific ion signature for unequivocal classification. Previous analysis of cow milk using the same liquid AP-MALDI MS methodology also demonstrated the detection of β-lactoglobulin at 18.3 kDa [ 29 ]. As is visible in the LDA loading plots of Figure 1 c and Figure 3 b,d, the differential detection of β-lactoglobulin proteoforms (e.g., m/z bins at 1513 and 1516, respectively) allowed the highly successful detection of 10% goat milk in sheep milk.…”
Section: Discussionmentioning
confidence: 99%